Pendampingan dalam Mengembangkan Minat Bakat Peserta Didik di MA Nurudz Dholam Patemon Kedungdung Sampang - tamam, Badrut; Nur Muhammad, Taufiqy (LP2M Institut Agama Islam Nazhatut Thullab Sampang, Indonesia, 2024)
Madrasah Aliyah Nurudz Dholam is strongly committed to optimizing student potential through developing interests and talents. With a proactive approach, this madrasah implements various special programs such as pencak silat training, English courses, and Arabic courses. The support and facilities provided help students develop their potential to the maximum. Based on this, the researcher focuses on three points, namely: First, How is the management of the principal in developing student interests and talents, Second, How is the effectiveness of the principal's management in developing student interests and talents, Third, How is the impact of the principal's management in developing student interests and talents on academic and non-academic achievements. The method used in this study is a Qualitative Method with a descriptive type, while data collection uses observation, interviews, and documentation. located at MA Nurudz Dholam Kedungdung Sampang. The results of the study indicate that: First, The success of the principal's management at Madrasah Aliyah Nurudz Dholam in developing student interests and talents is based on the application of four management components: planning, organizing, implementing, and supervising. The principal ensures that each of these aspects runs optimally through regular meetings, proper resource allocation, active leadership, and periodic evaluation. This approach creates an environment that supports educational goals. Second, The effectiveness of the principal's management at Madrasah Aliyah Nurudz Dholam can be seen from thorough planning, efficient implementation, and continuous monitoring and evaluation. This success is proven by student achievement in various fields, indicating that the programs being run are effective. The principal forms a team for special programs, ensures that resources are available and utilized properly, and provides continuous motivation and support to teachers. The principal ensures that the program remains effective and achieves educational goals. Third, At Madrasah Aliyah Nurudz Dholam, the principal creates an environment that supports the development of students' interests and talents through effective programs. These programs have a significant impact on honing students' potential in academic and non-academic fields, as evidenced by the achievements of students.